A novel multi-epitope vaccine of HPV16 E5E6E7 oncoprotein delivered by HBc VLPs induced efficient prophylactic and therapeutic antitumor immunity in tumor mice model. Issue 52 (12th December 2022) - Qi, Wang; Qingfeng, Li; Jing, Zhang; Maolin, Zheng; Zhihui, Zhang; Wangqi, Du; Shanli, Zhu; Jun, Chen; Pengfei, Jiang; Lifang, Zhang
Abstract: Human papilloma virus type 16 (HPV16) is the most prevalent etiologic agent associated with cervical cancer, and its early proteins E5, E6 and E7 play important roles in cervical epithelium transformation to cervical intraepithelial neoplasia and even cervical cancer. Hence, these oncoproteins are ideal target antigens for developing immunotherapeutic vaccines against HPV-associated infection and cervical cancer. Currently, multi-epitope vaccines have been a promising strategy for immunotherapy for viral infection or cancers. In this study, the E5aa28-46, E6aa37-57 and E7aa26-57 peptides were selected and linked to form a novel multi-epitopes vaccine (E765m), which was inserted into the major immune dominant region (MIR) of hepatitis B virus core antigen (HBc) to construct a HBc-E765m chimeric virus-like particles (cVLPs). The immunogenicity and immunotherapeutic effect of the cVLPs vaccine was evaluated in immunized mice and a tumor-bearing mouse model. The results showed that HBc-E765m cVLPs elicited high E5-, E6- and E7- specific CTL and serum IgG antibody responses, and also relatively high levels of the cytokines IFN-γ, IL-4 and IL-5. More importantly, the cVLPs vaccine significant suppressed tumor growth in mice bearing E5-TC-1 tumors. Our findings provide strong evidence that this novel HBc-E765m cVLPs vaccine could be a candidate vaccine for specific immunotherapy in HPV16-associated cervical intraepithelial neoplasia or cervical cancer.